Deconstructing Decolonising in the Context of a South African Higher Education Institution - Kehdinga George Fomunyam (E-Journal of Humanities, Arts and Social Sciences, 2023)
Decolonisation at its different levels and stages is a movement that started around the sixties and has swept across all continents of the world. However, there has been a re-invigoration of this movement in recent years on the African continent, particularly in the education sector. This took a different turn in South Africa in late 2015 when the #Mustfall movement started. Different institutions responded to this in a frenzy and the result was absolute chaos in both the understanding of the subject and response to it. About eight years later many academics are still grappling with the meaning of the consult and how to go about decolonising in higher education. Though there is a dearth of academic writing on the subject particularly in South Africa, this has translated to little action and the vestiges of colonialism remain. This paper sought to deconstruct decolonisation from an institutional perspective and theorise how the same can be made to unfold within the stratosphere. This study was designed as a qualitative case study of a South African University and used interviews as the data generation method. The findings indicated that decolonisation is about politics, language, and identity, not forgetting an element of confusion. The paper concluded that decolonisation has to transcend individual understandings of the same to deal with all facets of the higher education sector. It, therefore, recommended the adoption of a holistic approach to dealing with decolonisation and an overall improvement in the understanding of lecturers on decolonisation. This paper makes a vital contribution to the body of knowledge by articulating the conflicting understandings that exist and the confusion it breeds. It also points to the lack of decolonisation within the higher education space.